Spontaneous superficial femoral artery pseudoaneurysm: a rare case report - R., Naveenraj; Patel, Bhavin; Patel, Hiten; Tiwari, Ajay (International Surgery Journal, 2024)
Spontaneous femoral artery pseudoaneurysm (PSA) is a rare disease and there are few reported cases. We report a case of a 45 year-old male with painless, non-pulsatile swelling in the medial aspect of left lower thigh, which is gradually increasing in size for a period of 2 months. He had no history of trauma or surgery. CT Angiography confirmed a large pseudoaneurysm of the left distal superficial femoral artery (SFA). Then patient had sudden rupture of the pseudoaneurysm and it was treated surgically by ligation of SFA proximal and distal to pseudoaneurysm with excision of large surrounding hematoma.